Geoökologische Studien in der andinen Vulkankordillere und der zentralen Längssenke von Chile bei Chillán - Endlicher, Wilfried; Mardones, Maria (ERDKUNDE, 1988)
Studies of geomorphology, soil and vegetation cover have been undertaken at four different sites. In the Nevados of Chilian, a volcanic complex in the high cordillera, the Lenga forest has been extensively destroyed by forest fires and the construction of ski-fields and hotels. The risk of avalanches has therefore been increased. In the valley of the Rio Renegado, the volcanic ashes of its north-facing slopes are dissected by gullies. The secondary vegetation, an open bamboo scrub, cannot effectively protect the soil against water erosion. In the valley bottom the natural vegetation has been severely damaged by human impact (firewood cutting). On the south-facing slopes primary forest of Lenga and Coigiie can, however, still be found. The greatest landscape damage is shown in the north-facing and overgrazed slopes of the Montana, the Andean piedmont, where sheet and rill erosion is common. The remnants of the secondary Avellano-Rauli forest are often replaced by pine plantations. Finally, in the Central Depression, four main landscape units can be distinguished: laharic stone fields with espinal bush, moist valley bottoms, its terrace systems which are particularly suitable for artificial irrigation, and hilly terrain with a cover of loose, fine volcanic sands which are exposed to wind erosion